COMPARISON OF ARTERIAL BLOOD PRESSURE IN SICKLE CELL PATIENTS AND NON-SICKLE CELL YOUNG ADULTS IN ZARIA, KADUNA STATE NIGERIA - Abdulrauf, Rukayya A.; Farouk, A.; Adamu, J.; Nmadu, J. N.; Awwalu, S. (FUDMA JOURNAL OF SCIENCES, 2025)
The current study was aimed at evaluating the arterial blood pressure indices in young adults with (Sickle cell anemia) SCA in comparison to those with normal HbAA age- and sex-matched healthy controls. A sample size of 60 individuals aged 18-30 years were recruited for participation. They were divided into two groups; 30 being sickle cell patients (HbSS) as confirmed by hemoglobin electrophoresis and 30 being the control (HbAA) group. Consent was obtained from both groups and data was collected in a face-to-face administered questionnaire. The blood pressure in both groups were determined using a mercury sphygmomanometer and the results obtained showed that SCA patients had a significantly (p < 0.05) lower diastolic pressure and no difference (p > 0.05) was observed in systolic blood pressure. The mean arterial pressure was also found to be significantly (p < 0.05) lower in SCA patients than the normal. The sickle cell group exhibited a significantly (p < 0.05) higher heart rate and pulse pressure than the control group. In conclusion, sickle cell patients have a lower diastolic blood pressure and higher heart rate than non-sickle cell group. Therefore, as SCD patients transition into adulthood, they may not be at risk of hypertension and development of its various complications, but they may be prone to consequences of hypotension and bradycardia such as reduced cardiac output, reduced coronary hypoperfusion and cardiac arrhythmias.